1995
DOI: 10.1577/1548-8667(1995)007<0001:fcdcrs>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin-Contaminated Dietary Corn Reduced Survival and Antibody Production by Channel Catfish Challenged withEdwardsiella ictaluri

Abstract: Year-2 channel cattish Ictalurus punctatits (average initial weight. 31 g) were fed nutritionally balanced diets containing various amounts of corn culture material contaminated with the fungus Fusarium monilifonne. Quantities of culture material used provided 0.3 (control), 20, 80, 320, or 720 mg of the mycotoxin fumonisin B) (FB|) per kilogram of diet. Fish fed the two highest concentrations of FB| lost weight during the 14-week feeding period and experienced high mortality caused by Flexibacter columnaris. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…Registers of mycotoxin co‐occurrence in fish feeds are documented in the past for Egypt (Abdelhamid et al . ), United States (Lumlertdacha & Lovell ), Indonesia (Ali et al . ), Nigeria (Omodu Foluke Olorunfemi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Registers of mycotoxin co‐occurrence in fish feeds are documented in the past for Egypt (Abdelhamid et al . ), United States (Lumlertdacha & Lovell ), Indonesia (Ali et al . ), Nigeria (Omodu Foluke Olorunfemi et al .…”
Section: Resultsmentioning
confidence: 99%
“…All the aquaculture species tested for sensitivity to FUM to date (Ictalurus punctatus [Goel et al, 1994;Li, Raverty, & Robinson, 1994;Lumlertdacha & Lovell, 1995]; Oreochromis niloticus [Tuan et al, 2003]; Cyprinus carpio [Pepeljnjak et al, 2003;Petrinec et al, 2004]; and Oncorhynchus mykiss [Meredith, Riley, Bacon, Williams, & Carlson, 1998]) are freshwater species, and levels of sensitivity to FUM are usually higher than 10,000 μg/kg feed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the toxic dose for FB 1 in fish has a broad range, it is comparable with that for pigs and horses (Voss et al ). FB 1 causes mortality in fish either by direct tissue damage (Li et al ) or by immunosuppression that results in higher sensitivity to infection (Lumlertdacha and Lovell ; Pepeljnjak et al ). Chronic effects of FB 1 include a decrease in body weight gain and changes to hematological blood parameters.…”
Section: Fusarium Mycotoxinsmentioning
confidence: 99%
“…Channel catfish fed a diet with 80 mg/kg FB 1 displayed significantly lower disease resistance, expressed as higher mortality after infection with E . ictaluri , than similarly challenged catfish from a control group or those fed a diet with FB 1 20 mg/kg (Lumlertdacha and Lovell ). Pepeljnjak et al () observed a reduction in body weight gain in common carp fed 0.5 and 5.0 mg/kg FB 1 for 42 d, and a higher incidence of the bacterial infection erythrodermatitis cyprini in the group receiving 5.0 mg/kg FB 1 .…”
Section: Fusarium Mycotoxinsmentioning
confidence: 99%